Nitrazepam: lastingly effective but trouble on withdrawal. Issue 6025 (26th June 1976) - Adam, K; Adamson, L; Brezinová, V; Hunter, W M
Abstract : The sleep of 10 volunteers with an average age of 57 years was recorded electrophysiologically before, during, and after nitrazepam 5 mg nightly for 10 weeks. Sleep was longer and less broken on the drug and no tolerance was obvious after two months' use. Withdrawal of the drug, however, caused sleep to be temporarily worse than before the drug had been taken. Slow-wave sleep was reduced by nitrazepam, but the accompanying secretion of growth hormone was not impaired.